Analisis Sikap Serta Pengetahuan Pengemudi Bus dan Angkutan Umum Perkotaan di Surabaya terhadap Prinsip Safety Riding - Herman Bagus Dwicahyo; Neffrety Nilamsari; Sam Ramadhani Purmana; Deo Aji Winanto (Yayasan Literasi Sains Indonesia, 2026)
Traffic accidents remain a significant public health issue in Indonesia, with human factors identified as the dominant cause. The implementation of safety riding principles is essential to reduce accident rates, particularly among public transportation drivers who have high mobility and exposure to traffic risks. This study aimed to analyze the attitudes and knowledge of bus and urban public transportation drivers toward safety riding principles in Surabaya. A descriptive quantitative approach was employed by distributing structured questionnaires to 80 active drivers. Data were analyzed using descriptive statistics in the form of frequency and percentage distributions. The findings revealed that 47.5% of respondents correctly identified mirrors as tools to observe vehicles behind, 68.8% perceived traffic safety signs as adequately available, and 46.3% stated that discipline and compliance with traffic regulations are the key attitudes for safe driving. Regarding knowledge, 92.5% recognized the importance of wearing helmets, 93.8% understood safe overtaking procedures, and 97.5% prioritized pedestrians at zebra crossings. However, only 56.3% correctly identified the minimum speed limit on toll roads. In conclusion, the majority of respondents demonstrated good attitudes and knowledge regarding safety riding, although further educational reinforcement is needed, particularly on specific technical regulations.